2022
DOI: 10.1021/acsanm.2c01996
|View full text |Cite
|
Sign up to set email alerts
|

Cs3Cu2I5 Perovskite Nanoparticles in Polymer Matrix as Large-Area Scintillation Screen for High-Definition X-ray Imaging

Abstract: Perovskite scintillators have been widely used in X-ray detection; however, lead-based perovskite scintillators with strong self-absorption reduce the optical-coupling efficiency, significantly resulting in a relatively low optical yield. Herein, we prepared self-trapped exciton-emitting lead-free perovskite nanoparticles (Cs3Cu2I5) using a green antisolvent method and fabricated large-scale (Ø = 10 cm) scintillation screens by uniformly dispersing them in a transparent styrene monomer. The antisolvent optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…(e) Images of fish at different X-ray doses. 96 Copyright 2022 American Chemical Society. (f) Pulse height spectra of a Cs 3 Cu 2 I 5 : 6 Li crystal under 137 Cs and 252 Cf sources acquired by a model R6233-100 PMT.…”
Section: Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Images of fish at different X-ray doses. 96 Copyright 2022 American Chemical Society. (f) Pulse height spectra of a Cs 3 Cu 2 I 5 : 6 Li crystal under 137 Cs and 252 Cf sources acquired by a model R6233-100 PMT.…”
Section: Detectionmentioning
confidence: 99%
“…X-ray detectors based on CHP show high efficiency and accuracy, reflected in the high spatial resolution. The performance of some high energy ray detectors 46,49,56,78,96 based on CHP is illustrated in Fig. 14 and summarized in Table 3.…”
Section: Detectionmentioning
confidence: 99%
“…However, there are still some problems to be solved in order to achieve practical commercial applications of copper-based metal halide scintillators. First, the intrinsic poor stability makes metal halide scintillators exposed to the air, making it difficult to achieve long-term applications. , Second, the surface defects can hugely decrease the RL efficiency of scintillator nanocrystals (NCs), which makes it difficult to achieve high-resolution X-ray imaging. , The third issue is that currently most scintillator devices are packaged with a simple mixture of powder scintillators and polymers, which makes it difficult to obtain high-quality and uniform scintillator films. Based on this, the development of in-situ crystalline scintillator films can effectively solve the instability and packaging problems of copper-based metal halide and can also achieve flexible X-ray imaging. In our former research, it found that the CsPbBr 3 NCs can in-situ grow in precured polymer polymethyl methacrylate (PMMA) with high viscosity like as a “polymer ceramics”, which achieved flexible and high-resolution X-ray imaging .…”
Section: Introductionmentioning
confidence: 99%
“…35 Under X-ray radiation, copper-based perovskite scintillators exhibit high spatial resolution, excellent linear response, and low dose rate limit. [36][37][38] A 6 Li-doped Cs 3 Cu 2 I 5 single crystal has a light yield of 96 000 ph per neutron for thermal neutron radiation, which implies their potential in thermal neutron detection. 38 However, the neutron absorption efficiency of the crystal scintillator is restricted by the doping content, and the area of the scintillation screen is limited for some applications.…”
Section: Introductionmentioning
confidence: 99%